Biocompatibility and toxicity of graphene quantum dots for potential application in photodynamic therapy. (20th August 2018) - Tabish, Tanveer A; Scotton, Chris J; J Ferguson, Daniel C; Lin, Liangxu; der Veen, Anienke van; Lowry, Sophie; Ali, Muhammad; Jabeen, Farhat; Ali, Muhammad; Winyard, Paul G; Zhang, Shaowei
Aim: Achieving reliably high production of reactive oxygen species (ROS) in photodynamic therapy (PDT) remains challenging. Graphene quantum dots (GQDs) hold great promise for PDT. However, the photochemical processes leading to GQD-derived ROS generation have not yet been fully elucidated.Materials & methods: Physicochemical characteristics of GQDs were comprehensively investigated, including electron paramagnetic resonance analysis of singlet oxygen production. Dark toxicity was assessed in vitro and in vivo .Results: GQDs demonstrated excellent photoluminescent features, corrosion resistance, high water solubility, high photo/pH-stability, in vitro and in vivo biocompatibility and very efficient singlet oxygen/ROS generation.Conclusion: The enhanced ROS generation, combined with good biocompatibility and minimal toxicity in vitro and in vivo support the potential of GQDs for future PDT application.